Vaccine against human Papilloma Virus (Colombia Medica, 2014)
At present two prophylactic human papilloma virus (HPV) vaccines are commercially available. The Tetravalent vaccine against infection with four VPH types (6, 11, 16, and 18) distributed in the national program in Colombia and the Bivalent vaccine against the VPH types 16 and 18, respectively.  The efficacy and safety of both vaccines has periodically been assessed and they have been declared efficacious and safe by the health authorities of several countries and the Global Advisory Committee on Vaccine Safety ( GACVS ) of the World’s Health Organization (WHO).In its report of March 2014 the GACVS analyzed the evidence of the relationship between the  Human Papillomavirus Vaccine with  >175 million of doses distributed worldwide and autoimmune diseases, particularly Multiple Sclerosis, Aluminum as adjuvant, Vasculitis caused by vaccine DNA fragments and the Complex Regional Pain Syndrome described in Japan.   The Committee ratified the strict vaccine safety control and based on a thorough examination of existing evidence, reaffirmed that the risk-benefit profile remains favorable. The case of the children of Carmen de Bolivar in Colombia has been described by several authors in other countries as "Massive Psychogenic Event", which has absolute no relationship with the vaccine but its high media dissemination resulted into disastrous consequences for the national vaccination program